DIRECTIVE ACTS IN JAMES CORDEN "SPILL YOUR GUTS" TALKSHOW: PRAGMATICS APPROACH - Randy Sasanaputra; Zia Hisni Mubarak (BASIS (Bahasa dan Sastra Inggris), 2021)
The aimed of this research is to find out the kind of directive acts in James Corden’s talk show on YouTube channel entitled “Spill Your Guts” and the function of those directives acts that employed by the speaker. This research was categorized as descriptive qualitative research. The data sources of this research are from a talk show on James Corden’s YouTube channel which entitled “Spill Your Guts”. The data of this research was taken from the language used in conversation “Spill Your Guts”. The Researcher used the data script to analyze. The findings of the research show that there are three types of Directives acts, they are command, request, suggestion. There are 21 data that classified as command, 6 data classified as request and 8 data classified as suggestion. It can be shows that command is the most used directive acts employed by the speaker of this talk show. The reason why speaker employs directive acts in this talk show cannot be separated from the context of situations. The function of the directives performed by the speaker can be divided into four namely when the speaker wants to show his/her care about the hearer, wants to direct/instruct the hearer, wants to show his/her authority and also the speaker wants to warn the hearer.